PENGARUH STRATEGI PERCEIVED VALUE DALAM MEMBENTUK LOYALITAS PELANGGAN DI RUMAH SAKIT UNIVERSITAS HASANUDDIN KOTA MAKASSAR - Nursapriani Nursapriani; Muh Abduh Anwar; Andi Ilham Muchtar (PRAJA: Jurnal Ilmiah Pemerintahan, 2021)
The research aimed to analyze the perceived value of strategy effect with the functional value indicators (installation, service quality, price, and professionalism), emotional value (novelty, control, hedonics), and social value (prestige) in estabilishing the customer loyalty in Hasanuddin University Hospital, Makassar City. This was an explanatory descriptive research with cross sectional study design. Responden taken were as many as 100 people. Data were collected by an observation, questionnaire, and documentation. The data were analysed by descriptive statistics analysis namely by calculating the mean, percentage, frequency table, inferential statistics the through the chi-square, and multivariate analysis through the logistic regression analysis. The research result indicate that the functional values have the effect in establishing the customers’ loyalty, however, they are not significant of the customer loyalty but low significant (p = 0.023, exp (B) = 3.179), emotional values have the effect in establishing the customers’ loyalty and they are significant (p = 0.002, exp (B) = 33.250), and social values have the effect in establishing the customers’ loyalty and it is very significant (p = 0.000, exp (B) = 40.969). the social value variable is the most influential variable in establishing the longstay customers’ loyalty in the Teaching Hospital of Hasanuddin University, Makassar City.